Identification of CDK2 substrates in human cell lysates - Chi, Yong (BioMed Central, 2008)
BACKGROUND: Protein phosphorylation regulates a multitude of biological processes. However, the large number of protein kinases and their substrates generates an enormously complex phosphoproteome. The cyclin-dependent kinases - the CDKs - comprise a class of enzymes that regulate cell cycle progression and play important roles in tumorigenesis. However, despite intense study, only a limited number of mammalian CDK substrates are known. A comprehensive understanding of CDK function requires the identification of their substrate network. RESULTS: We describe a simple and efficient approach to identify potential cyclin A-CDK2 targets in complex cell lysates. Using a kinase engineering strategy combined with chemical enrichment and mass spectrometry, we identified 180 potential cyclin A-CDK2 substrates and more than 200 phosphorylation sites. About 10% of these candidates function within pathways related to cell division, and the vast majority are involved in other fundamental cellular processes. We have validated several candidates as direct cyclin A-CDK2 substrates that are phosphorylated on the same sites that we identified by mass spectrometry, and we also found that one novel substrate, the ribosomal protein RL12, exhibits site-specific CDK2-dependent phosphorylation in vivo. CONCLUSIONS: We used methods entailing engineered kinases and thiophosphate enrichment to identify a large number of candidate CDK2 substrates in cell lysates. These results are consistent with other recent proteomic studies, and suggest that CDKs regulate cell division via large networks of cellular substrates. These methods are general and can be easily adapted to identify direct substrates of many other protein kinases.